PENGEMBANGAN APLIKASI PENGENALAN RUMAH ADAT SUMATERA BERBASIS AUGMENTED REALITY - Aliy Hafiz (Jurnal Teknologi dan Informatika (JEDA), 2020)
AbstractAugmented Reality (AR) is a technology that combines virtual objects into a real environment in real time. Augmented Reality is applied in various fields, one of which is in education as a learning medium. In this research, Augmented Reality technology is included in the fruit recognition book in early childhood with the aim of making this fruit recognition learning media for early childhood more interesting and interactive. The application is designed and then realized using functions in the ARTool Library for camera activation, tracking markers and displaying 3D virtual objects from the fruit on the markers contained in the fruit recognition book.